2018
DOI: 10.1177/1559325818760880
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity of Cypermethrin in Hepatocarcinoma Cells: A Dose- and Time-Dependent Study

Abstract: Most of the agricultural workers are potentially exposed to pesticides through different routes. Inhalation exposures may result in numerous diseases that can adversely affect an individual’s health and capacity to perform at work. The aim of this study was to determine the cytotoxic potential of cypermethrin pesticide on cultured human hepatocarcinoma (HepG2) cells. The HepG2 cells were exposed to cypermethrin (0, 5, 15, 40 ng/mL) for 24 and 48 hours. We observed that cypermethrin caused cell death of HepG2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
1
3
1
Order By: Relevance
“…The elevated levels of these enzymatic antioxidants may be a compensatory response to combat and mitigate the toxic effects of increased CYP superoxide radical and other ROS generation. Our findings were in agreement with AlKahtane et al [51] who reported that SOD and CAT levels were increased in cultured human hepatocarcinoma (HepG2) cells following CYP exposure. Also, our results in consonance with Khan et al [32] who reported an increase in GST activity in the brain tissue of rats exposed to deltamethrin (another synthetic type II pyrethroid).…”
Section: Resultssupporting
confidence: 93%
“…The elevated levels of these enzymatic antioxidants may be a compensatory response to combat and mitigate the toxic effects of increased CYP superoxide radical and other ROS generation. Our findings were in agreement with AlKahtane et al [51] who reported that SOD and CAT levels were increased in cultured human hepatocarcinoma (HepG2) cells following CYP exposure. Also, our results in consonance with Khan et al [32] who reported an increase in GST activity in the brain tissue of rats exposed to deltamethrin (another synthetic type II pyrethroid).…”
Section: Resultssupporting
confidence: 93%
“…These results are in line with the data from other studies where TBT in human HepG2 (Zeng et al, 2018) and fish RTG-2 (Giltrap et al, 2011) cells or CBZ in human A549 cells (Tollstadius et al, 2019) caused cytotoxicity in similar concentrations. Similarly, CP caused cytotoxicity in HepG2 cells (AlKahtane et al, 2018) and in five fish cell lines, namely Etroplus suratensis, Labeo rohita, and Channa stratus gill cell lines, and Catla catla brain and gill cell lines (Taju et al, 2014); however, the observed cytotoxicity was caused by lower concentrations of CP (10 -8 M) after 24 h compared to our data. BPA, ATR, and MZ caused no cytotoxic response in HepG2 and RTL-W1 cells.…”
Section: Discussioncontrasting
confidence: 71%
“…After treatment, the cells were incubated with Rhodamine 123 (20 μmol/L; Cayman chemical) for 40 minutes at 37°C, rinsed, and images were obtained by fluorescence microscope, and fluorescent intensity of control and treated cells were read by using the microplate reader. 22 …”
Section: Methodsmentioning
confidence: 99%